The Influence Of Price Perception, Taste, And Location On Customer Satisfaction (Survey On Customers Of Café Shelter Wisata Galunggung) - Wulan Nursarah; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (Journal of Indonesian Management, 2022)
This study aims to determine the effect of perception of price, taste, and location of sales on customer satisfaction at Café Shelter Wisata Galunggung Tasikmalaya. The method used in this research is a quantitative approach method with a survey method. The population in this study is unknown and the sample is taken using random sampling. While the determination of the number of respondents (samples) using purposive sampling as many as 100 respondents. The analytical tool used is multiple regression analysis. SPSS version 25 is used. The results show that price perception and taste simultaneously have a significant influence on customer satisfaction. Price perception partially has a significant influence on customer satisfaction. Taste partially has a significant influence on customer satisfaction. The sales location partially has no significant influence on customer satisfaction.